2005
DOI: 10.1007/s00125-005-1832-1
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in childhood and adolescent type 1 diabetes: early disease, early treatment?

Abstract: Autopsy studies have shown that atherosclerosis begins in adolescence in otherwise healthy individuals, and imaging techniques have shown that atherosclerosis develops earlier and is more prevalent in children with diabetes than in age-matched healthy controls. Cardiovascular disease has now overtaken diabetic nephropathy as the leading cause of premature mortality in young adults with diabetes, and the emphasis on disease prevention has accordingly shifted to a younger age group. The majority of children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 98 publications
3
102
0
8
Order By: Relevance
“…HbA 1c was lower among 9-10-yearolds than among 12-13-year-olds. Serum lipids were within target levels to prevent cardiovascular disease [1], except for LDL-cholesterol among girls in the 9-10-year-old age group, which was above the recommended level (Table 1). No significant differences were found in the duration of education between the parents of diabetic subjects and those of control subjects (fathers' education: p=0.50, mothers' education: p = 0.18).…”
Section: Subject Recruitment and Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…HbA 1c was lower among 9-10-yearolds than among 12-13-year-olds. Serum lipids were within target levels to prevent cardiovascular disease [1], except for LDL-cholesterol among girls in the 9-10-year-old age group, which was above the recommended level (Table 1). No significant differences were found in the duration of education between the parents of diabetic subjects and those of control subjects (fathers' education: p=0.50, mothers' education: p = 0.18).…”
Section: Subject Recruitment and Characteristicsmentioning
confidence: 92%
“…It is well established that type 1 diabetic children and adolescents have an increased risk of cardiovascular disease compared to the general population [1,2]. The multi-centre study EURODIAB found that low intake of saturated fat and high intake of fibre reduced the risk of cardiovascular disease among type 1 diabetic subjects [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with type 1 diabetes are at higher risk of developing CVD than the general population (19), and long-term blood glucose control is a strong predictor for CVD in type 1 diabetes (20 -22). The development of atherosclerosis starts early in life (19).…”
mentioning
confidence: 99%
“…As Knut Dahl-Jørgensen and colleagues point out in their accompanying review [20], type 1 diabetes carries the same risk of premature arterial disease as familial hypercholesterolaemia, and cardiovascular disease has overtaken diabetic nephropathy as the leading cause of premature mortality in individuals over the age of 30 [21]. They describe postmortem studies that identified fatty streaks in 100% of aortas and 50% of right coronary arteries in non-diabetic individuals who died between the age of 15 and 19 years [22], and thickening of the intima-media in the aorta and carotid arteries has been described in 11-year-old children with diabetes as compared with non-diabetic control subjects [23].…”
mentioning
confidence: 97%